A comparison of efficacy between 0.2% of topical glyceryl trinitrate and lateral anal sphincterotomy - Paul, Vivian Anandith; Nagesh Reddy, Katpally; Sarath Chandra, Alluru (International Surgery Journal, 2020)
Background: Anal fissure is a linear tear in the lining of the anal canal below the dentate line. Among the conservative modalities glyceryl trinitrate (GTN) is emerging as first line of treatment since it breaks the vicious cycle and relaxes the sphincter. Surgery was considered as the first line of treatment if conservative measures such as bulk laxatives, stool softeners and local anaesthetics fail. Aim of this study was to study the aetiology and predisposing factors, age and sex distribution, clinical presentation, position of fissure, complications associated with medical and surgical management and comparison of efficacy of topical GTN (0.2%) and lateral anal sphincterotomy. Methods: The study was based on analysis of 60 patients who were treated for chronic fissure in ano at Malla Reddy Institute of Medical Sciences, Hyderabad from January 2018 to February 2020. Patients were divided into 2 groups. One group was managed by topical application of the ointment and other group was managed by surgery (lateral anal sphincterotomy). Statistical tool (software) used to analyse the data was SPSS 13.0 software. Results: Around 33.33% patients who were managed medically by 0.2% glyceryl trinitrate did not have relief of symptoms. Patients under surgical management had more relief of symptoms (86.6%). Almost all patients treated with glyceryl trinitrate had some form of headache. During the immediate post-operative period 13.3% patients treated with surgery had pain. Conclusions: It can be concluded that open lateral anal sphincterotomy is superior to topical 0.2% GTN with high rate of healing and very low rate of complications.